2011
DOI: 10.1016/j.ijsolstr.2010.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectric properties of ferroelectrics and the nanoindentation size-effect

Abstract: a b s t r a c tRecent works have established the critical role of flexoelectricity in a variety of size-dependent physical phenomena related to ferroelectrics including giant piezoelectricity at the nanoscale, dead-layer effect in nanocapacitors, dielectric properties of nanostructures among others. Flexoelectricity couples strain gradients to polarization in both ordinary and piezoelectric dielectrics. Relatively few experimental works exist that have determined flexoelectric properties and they all generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 33 publications
(36 reference statements)
2
31
0
Order By: Relevance
“…In particular, the electrostatic cost of generating flexoelectric charge causes a depth-dependent stiffening in nanoindentation experiments, owing to the very inhomogeneous nature of the stress introduced by a nanoindenter. This effect was studied both experimentally and theoretically for several materials by the Texas group [78][79][80]. By measuring the curvature ζ induced by the electric field E, one can also get an estimate of the flexoelectric coefficient which is given bỹ…”
Section: Elasticity and Lattice Dynamicsmentioning
confidence: 99%
“…In particular, the electrostatic cost of generating flexoelectric charge causes a depth-dependent stiffening in nanoindentation experiments, owing to the very inhomogeneous nature of the stress introduced by a nanoindenter. This effect was studied both experimentally and theoretically for several materials by the Texas group [78][79][80]. By measuring the curvature ζ induced by the electric field E, one can also get an estimate of the flexoelectric coefficient which is given bỹ…”
Section: Elasticity and Lattice Dynamicsmentioning
confidence: 99%
“…Note that in all locations the offset component shows pronounced hysteresis with an "ideal" loop shape. However, the hysteresis loops are significantly shifted in the vertical direction, either due to the presence of frozen polarization layers, 84,85,108 non-uniform stress effects, 106,[109][110][111][112] or contribution of nonlocal bimorph modes. 113 The relaxing part shows almost complete lack of hysteresis, similar to the tip-electrode data in Sec.…”
Section: Relaxation In a Capacitor Structurementioning
confidence: 99%
“…The continuum theory incorporating the effects of flexoelectricity identified some unexpected manifestations of this phenomenon. For example, Gharbi et al (2011) identified an important role of flexoelectricity in the hardening of ferroelectrics at nano-indentation. Morozovska et al (2011) showed that the flexoelectric effect can play an important role in the electromechanical properties of moderate conductors.…”
Section: Introductionmentioning
confidence: 99%